DL-3n-Butylphthalide Improves Blood–Brain Barrier Integrity in Rat After Middle Cerebral Artery Occlusion - Mamtilahun, Muyassar; Wei, Zhenyu; Qin, Chuan; Wang, Yongting; Tang, Yaohui; Shen, Fan-xia; Tian, Heng-Li; Zhang, Zhijun; Yang, Guo-Yuan (Frontiers in Cellular Neuroscience, 2021)
Objective: Dl-3n-butylphthalide (NBP) has beneficial effects in different stages of ischemic stroke. Our previous studies have demonstrated that NBP promoted angiogenesis in the perifocal region of the ischemic brain. However, the molecular mechanism of NBP for blood-brain barrier protection in acute ischemic stroke was unclear. Here, we explored the neuroprotective effects of NBP on blood-brain barrier integrity in the acute phase of ischemic stroke in a rat model. Methods: Adult male Sprague-Dawley rats (n=82) underwent 2 hours of transient middle cerebral artery occlusion and received 90 mg/kg NBP for 3 days. Brain edema, infarct volume, surface blood flow, and neurological severity score were evaluated. Blood-brain barrier integrity was evaluated by Evans blue leakage and changes in tight junction proteins. We further examined AQP4 and eNOS expression, MMP-9 enzyme activity, and possible signaling pathways for the role of NBP after ischemic stroke. Results: NBP treatment significantly increased eNOS expression and surface blood flow in the brain, reduced brain edema and infarct volume, and improved neurological severity score compared to the control group (p<0.05). Furthermore, NBP attenuated Evans blue and IgG leakage and increased tight junction protein expression compared to the control after 1 and 3 days of ischemic stroke (p<0.05). Finally, NBP decreased AQP4 expression, MMP-9 enzyme activity, and increased MAPK expression during acute ischemic stroke. Conclusion: NBP protected blood-brain barrier integrity and attenuated brain injury in the acute phase of ischemic stroke, by decreasing AQP4 expression and MMP-9 enzyme activity. The MAPK signaling pathway may be involved in this process.